2002
DOI: 10.1023/a:1020543004400
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2/bcl-xL Bispecific Antisense Treatment Sensitizes Breast Carcinoma Cells to Doxorubicin, Paclitaxel and Cyclophosphamide

Abstract: Overexpression of the anti-apoptotic proteins bcl-2 and bcl-xL is implicated in breast cancer development, tumor progression and drug resistance. Here we describe the use of the bcl-2/bcl-xL bispecific antisense oligonucleotide 4625 to sensitize breast carcinoma cells to anti-cancer drugs routinely used in breast cancer therapy. MCF7 cells were treated with oligonucleotide 4625, doxorubicin, paclitaxel or cyclophosphamide alone, or with combinations of oligonucleotide and the anti-cancer drugs. As measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…Lorenzo and coworkers [35] have reported that doxorubicin-induced apoptosis includes a downregulation of Bcl-2 protein and involvement of the mitochondrial pathway. Overexpression of Bcl-xL has been observed to protect cardiomyocytes from doxorubicin-provoked apoptosis [50,51], and bcl-2/bcl-xL bispecific antisense treatment has been found to sensitize breast carcinoma cells to doxorubicin [52], suggesting an important survival function for Bcl-2 and/or Bcl-xL in cells exposed to doxorubicin.…”
Section: Doxorubicin-induced P38 Mapk Activation Negatively Regulatesmentioning
confidence: 99%
“…Lorenzo and coworkers [35] have reported that doxorubicin-induced apoptosis includes a downregulation of Bcl-2 protein and involvement of the mitochondrial pathway. Overexpression of Bcl-xL has been observed to protect cardiomyocytes from doxorubicin-provoked apoptosis [50,51], and bcl-2/bcl-xL bispecific antisense treatment has been found to sensitize breast carcinoma cells to doxorubicin [52], suggesting an important survival function for Bcl-2 and/or Bcl-xL in cells exposed to doxorubicin.…”
Section: Doxorubicin-induced P38 Mapk Activation Negatively Regulatesmentioning
confidence: 99%
“…tumor size) may correlate more directly to the progression of the disease. The huge amount of information embedded in genome-wide studies should, in principle, allow for extraction of both kind of markers in gene expression data, but it is not inconceivable that genome-wide profiling is more related to disease subtypes (16,42) than to progression. If so, gene expression analysis may be better suited for studies aiming at an improved biological insight to the mechanisms behind the studied disease and its subtypes, potentially leading to the discovery of new drug targets and development of new therapeutic protocols.…”
Section: Discussionmentioning
confidence: 99%
“…To find the reporters on our array corresponding to the genes on our pre-defined gene lists, we used the official gene symbol. The gene symbols for the van 't Veer gene list (16) were obtained through ACID (39) using UniGene build 176, and the official gene symbols for the drug-genes were found manually using Gene and Locus Link. All reporters on our array that according to UniGene build 180 had a gene symbol represented on the resulting list were selected.…”
Section: Search Strategy and Selection Criteria For Drug Associated Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer gene therapy has generally been considered to be tumorostatic, thus implying that the predominant mechanism is involved in the induction of cell death or apoptosis. 28,29 Recently, however, there have been several studies showing that breast cancer is to some extent a cell cycle disease. 30,31 The cell cycle coordination takes place mainly at G 1 /S and G 2 /M phase transitions by a series of checkpoints.…”
Section: Discussionmentioning
confidence: 99%